Facile Synthesis of Curcumin-Loaded Starch-Maleate Nanoparticles - Pang, S.C.; Tay, S.H.; Chin, S.F. (Hindawi Publishing Corporation, 2014)
We have demonstrated the loading of curcumin onto starch maleate (SM) under mild conditions by mixing dissolved curcumin and SM nanoparticles separately in absolute ethanol and ethanol/aqueous (40 : 60 v/v), respectively. Curcumin-loaded starch-maleate (CurSM) nanoparticles were subsequently precipitated from a homogeneous mixture of these solutions in absolute ethanol based on the solvent exchange method. TEM analysis indicated that the diameters of CurSM nanoparticles were ranged between 30 nm and 110 nm with a mean diameter of 50 nm. The curcumin loading capacity of SM as a function of loading duration was investigated using the UV-visible spectrophotometer. The loading of curcumin onto SM increased rapidly initially with loading duration, and the curcumin loading capacity of 15 mg/g was reached within 12 hours. CurSM nanoparticles exhibited substantially higher water solubility of 6.0 × 10−2 mg/mL which is about 300 times higher than that of pure curcumin. With enhanced water solubility and bioaccessibility of curcumin, the potential utility of CurSM nanoparticles in various biomedical applications is therefore envisaged.